Agile Development in the Age of Adaptive Management - and Davis, Taryn; Orton-Vipond, Sarah; Staid, Martha (2019)
Adaptive management – the idea that development projects should respond to real life complexities and be flexible enough to respond to unforeseen changes – is an often-praised approach to doing development differently, with donors and partners exploring how to apply it within their programming.